The Effect of New Business Formation on Regional Development - Fritsch, Michael (The Wiley Handbook of Entrepreneurship, 2017)
Summary This chapter reviews the current state of knowledge about the effects of new business formation on regional development. These effects are diverse and include the creation and destruction of employment, introduction of innovations, structural change, and increasing productivity, among others. The chapter provides an explanatory approach that highlights the competitive challenge that start‐ups pose to incumbent firms and discusses important implications. The overview of empirical research particularly deals with the development of start‐up cohorts, identification of different types of indirect effects and their magnitude, differences based on characteristics of entry, and regional variation. A general conclusion is that the diverse indirect effects of new business formation on development tend to be much more important than the direct contribution of the newcomers in terms of job creation and additional value added. The diverse indirect effects of entry on development are currently less than fully understood. The chapter ends by drawing conclusions for policy and puts forward a number of important questions for further research.
Keywords: employment; entrepreneurship; new business formation; regional development